Exploring motion concepts to images as multimodal factors in nonverbal language - Agustina Kusuma Dewi; Levita Dwinaya (IRecall Journal, 2024)
The scarcity of research concerning the incorporation of motion as a modality within non-verbal language imagery has posed challenges in establishing comprehensive measures for evaluating the reliability of its application in content construction. In an effort to pinpoint the factors associated with the implementation of the motion concept in images, the authors undertook a series of pre-experimental research stages. Several data sets subjected to analysis were generated through pre-experimental studies, involving the formulation of questionnaire instruments employing convenience sampling techniques. The outcomes underwent significance testing utilizing Chi-Square and Single Factor analysis. Nevertheless, when delving into the application of the Motion Concept within images, certain aspects have yet to be taken into consideration. Specifically, the utilization of Stimuli and Novelty Intensity factors to shape visual elements, as well as the integration of quasi-experimental research employing more robust sampling techniques, merit attention. Additionally, the impact of cultural modalities on the application of motion concepts to imagery as one of multimodal factor in nonverbal language; necessitates further exploration and evaluation.